A Human-Derived Monoclonal Antibody Targeting Extracellular Connexin Domain Selectively Modulates Hemichannel Function - Ziraldo, Gaia; Buratto, Damiano; Kuang, Yuanyuan; Xu, Liang; Carrer, Andrea; Nardin, Chiara; Chiani, Francesco; Salvatore, Anna Maria; Paludetti, Gaetano; Lerner, Richard A.; Yang, Guang; Zonta, Francesco; et al. (Frontiers in Physiology, 2019)
Connexin hemichannels, which are plasma membrane hexameric channels (connexons) composed of connexin protein protomers, have been implicated in a host of physiological processes and pathological conditions. A number of single point pathological mutations impart a “leaky” character to the affected hemichannels, i.e., make them more active or hyperactive, suggesting that normal physiological condition could be recovered using selective hemichannel inhibitors. Recently, a human-derived monoclonal antibody named abEC1.1 has been shown to inhibit both wild type and hyperactive hemichannels composed of human (h) connexin 26 (hCx26) subunits. The aims of this work were (1) to characterize further the ability of abEC1.1 to selectively modulate connexin hemichannel function and (2) to assess its in vitro stability in view of future translational applications. In silico analysis of abEC1.1 interaction with the hCx26 hemichannel identified critically important extracellular domain amino acids that are conserved in connexin 30 (hCx30) and connexin 32 (hCx32). Patch clamp experiments performed in HeLa DH cells confirmed the inhibition efficiency of abEC1.1 was comparable for hCx26, hCx30 and hCx32 hemichannels. Of note, even a single amino acid difference in the putative binding region reduced drastically the inhibitory effects of the antibody on all the other tested hemichannels, namely hCx30.2/31.3, hCx30.3, hCx31, hCx31.1, hCx37, hCx43 and hCx45. Plasma membrane channels composed of pannexin 1 were not affected by abEC1.1. Finally, size exclusion chromatography assays showed the antibody does not aggregate appreciably in vitro. Altogether, these results indicate abEC1.1 is a promising tool for further translational studies.